cis-Dichloridobis(N,N,N′,N′-tetramethylethane-1,2-diamine)platinum(II) - Abdullah M. Asiri; Muhammad Nadeem Arshad; Muhammad Ishaq; Khalid A. Alamry; Tanveer Hussain Bokhari (Acta Crystallographica Section E, 2012)
In the title complex, [PtCl2(C6H16N2)], the PtII atom adopts a distorted cis-PtN2Cl2 square-planar coordination geometry. The five-membered chelate ring adopts a twisted conformation. In the crystal, weak C—H...Cl hydrogen bonds link the molecules into (001) sheets.